2018
DOI: 10.1371/journal.pone.0190800
|View full text |Cite
|
Sign up to set email alerts
|

MAFB is dispensable for the fetal testis morphogenesis and the maintenance of spermatogenesis in adult mice

Abstract: The transcription factor MAFB is an important regulator of the development and differentiation of various organs and tissues. Previous studies have shown that MAFB is expressed in embryonic and adult mouse testes and is expected to act as the downstream target of retinoic acid (RA) to initiate spermatogenesis. However, its exact localization and function remain unclear. Here, we localized MAFB expression in embryonic and adult testes and analyzed its gene function using Mafb-deficient mice. We found that MAFB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…The analysis also revealed genes encoding for transcription factors such as Tgfb1, Tgfb3, Tcf7 , and Mafb , where the former is considered to be expressed by the Sertoli cells and may be important for spermatogenesis (Memon et al, 2008), while, regarding the latter, studies in mice show that it is indispensable for the fetal testis morphogenesis and the maintenance of spermatogenesis (Shawki et al, 2018). The female-biased gonochoristic-specific genes included, among others, the TATA binding proteins Taf8 and Taf15 , the cytochoromic enzymes Cyp20a and Spdl1 that is also a female-biased gene in the guppy, Poecilia reticulata (Sharma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also revealed genes encoding for transcription factors such as Tgfb1, Tgfb3, Tcf7 , and Mafb , where the former is considered to be expressed by the Sertoli cells and may be important for spermatogenesis (Memon et al, 2008), while, regarding the latter, studies in mice show that it is indispensable for the fetal testis morphogenesis and the maintenance of spermatogenesis (Shawki et al, 2018). The female-biased gonochoristic-specific genes included, among others, the TATA binding proteins Taf8 and Taf15 , the cytochoromic enzymes Cyp20a and Spdl1 that is also a female-biased gene in the guppy, Poecilia reticulata (Sharma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Blood vessels might also be included in the interstitial compartment. To conclude, it is most appropriate to purify the subsets of testis cells using fluorescence-activated cell sorting/magnetic-activated cell sorting in combination with a reporter strain animal [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to immune cell expression, both MAFB and MAF are early markers of interstitial mesenchymal cells in both sexes [9], and in later stages of fetal development MAFB is expressed in both Leydig and Sertoli cells [39]. Knock-in mutant analyses and global conditional deletion of Mafb revealed that it was not required for fetal testicular differentiation or for maintenance of adult spermatogenesis [39]. However, multiple studies have suggested that Mafb and Maf have redundant or overlapping roles [27,41], perhaps due to similar and conserved DNA binding domains [38,42,43]; additionally, Mafb;Maf double homozygous knockout embryos have earlier embryonic lethality than other combinations of large Maf genes [44], indicating that these genes have essential, redundant roles in embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, MAFB and MAF, but not MAFA, are expressed in the fetal gonad [9,39]. MAF is expressed in macrophages within the developing gonad-mesonephros complex [8], and MAFB has been well-characterized as a marker of monocyte-derived myeloid cells [29,40].…”
Section: Introductionmentioning
confidence: 99%